Coordination of Regional Disaster Management Agencies In Providing Logistics and Disaster Management Equipment In Gunung Mas District, Central of Kalimantan - Iputrajaya Iputrajaya; Andi Tenri Sompa; Jamaluddin Jamaluddin (Wadah Inovasi Indonesia, 2021)
This study aims to determine how the coordination of regional disaster management agencies in providing logistics and equipment for disaster management in Gunung Mas district, Central Kalimantan province, from the elements of time management, synchronization, shared interests, and common goals in coordination. The method used in this research is qualitative. Data collection techniques are by using interviews, observation, and documentation study. Meanwhile, data analysis was carried out through three activity streams which were an interrelated unit, namely data reduction, data presentation and conclusion drawing. Based on the results of the research, it found that the coordination carried out by the Regional Disaster Management Agency in the provision of logistics and equipment from the aspects of time management and timeliness, synchronization, shared interests, and common goals have been well-coordinated by the system. Pattern as well as the applicable provisions, namely when pre-disaster, emergency response, and post-disaster, the only obstacle in this coordination is different lines of command or different work units among other related agencies. This research concludes that the coordination of the Regional Disaster Management Agency of Gunung Mas Regency in the provision of logistics and equipment for disaster management in Gunung Mas Regency has been well-coordinated according to the existing system and the prevailing patterns and regulations. These obstacles in coordination are greatly influenced by the lack of understanding from other relevant agencies regarding their duties, powers and responsibilities for disaster management. The next inhibiting factor is that the service/agency/other institution does not have a hierarchical relationship (line of command) due to different work units, resulting in less than optimal coordination.